Analytical modelling of the shear behaviour of rock joints with progressive degradation of two‐order roughness. (2nd September 2019) - Li, Yingchun; Liang, Zhengzhao; Tang, Chun'an; Li, Danqi; Wu, Chuangzhou
Summary: We present an analytical model for the shear behaviour of rock joints with progressive degradation of two‐order asperities including waviness and unevenness. Critical waviness and critical unevenness are used to respectively represent the mechanical involvements of waviness and unevenness during shear. The degradation process of two‐order asperities are predicted by considering the stepwise relationship among dilation angle, sheared and unsheared asperity areas, and plastic tangential work. The dilation angle of each asperity decreases as plastic tangential work accumulates. The progressive degradation transiting from critical unevenness to critical waviness is realised through examining the dilation angle and the unsheared area of critical unevenness. The model's predictions are compared with the experimental data from direct shear tests on both regular‐ and irregular‐shaped joints. Good agreement between analytical and experimental curves demonstrate the credence of the proposed model. Therefore, the model, after implemented in finite and discrete element codes, is practicable for the stability assessment of rock‐engineering structures.